Огляд принципів позиціонування автономного автомобільного транспорного засобу у просторі - Кривицький, А. О. (ХНУРЕ, 2020)
The given work is devoted to positioning sensors in modern developments of autonomous driving vehicles. Work describes radars, lidars, and work with video stream. Problems with lidars, combinations of different sensors. Current status of autonomous driving vehicles and their future.
Keywords: точність позиціонування автомобіля; радар; електромагнітні хвилі; лідари